The suitability of internal combustion engine sounds as artificial warning sounds for electric and hybrid vehicles - Ivan Bolkovac; Marko Horvat; Kristian Jambrošić; Hrvoje Domitrović (Promet - Traffic&Transportation, 2014)
The paper discusses the issue of adding artificial warning sounds to hybrid and fully electric vehicles, in order to increase traffic safety by making these vehicles audible at low speeds. The goal of this modification is to enable the pedestrians to perceive possible danger coming from such a vehicle in time to respond accordingly. Following the results of previous research which state that the sounds of internal combustion engines are valid candidates for artificial warning sounds to be added to hybrid or fully electric vehicles, a preliminary examination of the suitability and acceptability of different engine sounds in various modes of operation has been conducted. The chosen modes of operation are running in idle, at 2000 rpm and 3000 rpm with the vehicle stopped. Both gasoline and diesel engines were investigated. To expand the range of engine sounds, the type of vehicles was not limited to personal cars. The results show significant differences in suitability of engine sounds for the stated purpose, with vehicle type being the main differentiating factor.